Sulphur isotope and trace element signatures within mineralised occurrences in the Fraser Zone, Western Australia - Walker, Alexander Thomas (Curtin University, 2019)
This thesis uses trace element and sulphur isotope signatures to constrain processes forming and modifying mineralisation within the Fraser Zone of the Albany-Fraser Orogen, in Western Australia. Results indicate a complex record of mixed sulphur sources, including Archaean sulphur, within the Fraser Zone. Despite post-mineralisation modification of ore associated with metamorphism, the Fraser Zone remains highly prospective for economic mineralisation and further exploration will aid discovery of a diverse range of mineralisation styles.